2006
DOI: 10.1001/archsurg.141.6.581
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Survival After Radiofrequency Ablation of Complex Unresectable Liver Tumors

Abstract: Hypothesis: Radiofrequency ablation (RFA) may improve survival of high-risk patients with unresectable and refractory tumors.Design: Retrospective analysis of a prospective database.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 27 publications
3
77
0
2
Order By: Relevance
“…Radiofrequency ablation therapy in the treatment of small renal tumors has been an alternative to other methods of treatment due to high radiological and oncological efficacy [2]. Radiofrequency ablation therapy is applied with success in the treatment of liver, kidney, lung, bone and breast tumors [3]. Radiofrequency ablation therapy can be performed to treat small renal cell carcinoma by both percutaneous and laparoscopic approaches.…”
Section: Sirmentioning
confidence: 99%
“…Radiofrequency ablation therapy in the treatment of small renal tumors has been an alternative to other methods of treatment due to high radiological and oncological efficacy [2]. Radiofrequency ablation therapy is applied with success in the treatment of liver, kidney, lung, bone and breast tumors [3]. Radiofrequency ablation therapy can be performed to treat small renal cell carcinoma by both percutaneous and laparoscopic approaches.…”
Section: Sirmentioning
confidence: 99%
“…Although the approach of RFA was not shown to influence survival, there was a trend towards a higher rate of recurrence with percutaneous RFA (PcRFA) (15.1%) compared to open (6.7%) and laparoscopy (9%) in a study by Bleicher et al of 153 patients treated for a total of 447 liver tumours [8]. In addition, several studies had consistently reported significantly higher complication rates with PcRFA relative to operative approaches [9,10]. Despite the perceived technical simplicity with PcRFA, the cooperation of patients' respiratory effort following sedation poses difficulty in accurate probe placement [11].…”
Section: Delivery Of Rfamentioning
confidence: 99%
“…Radiofrequency ablation (RFA) is an important and minimal-invasive treatment option for hepatic tumors and metastases [1][2][3][4][5][6][7]. It belongs to the energy-based ablation modalities and relies on proper needle electrode placement into the tumor via an open, laparoscopic or percutaneous approach.…”
Section: Introductionmentioning
confidence: 99%